Corporate social responsibility (CSR) and earnings management: A structured literature review with a focus on contextual factors - Patrick Velte (Corporate Social Responsibility and Environmental Management, 2024)
Abstract The link between corporate social responsibility (CSR) and earnings management represents an attractive empirical research topic in recent years. In view of the heterogeneous research results, the purpose of this structured literature review is to analyze the contextual factors of this complex relationship. We selected 107 quantitative peer-reviewed archival studies on that topic and explain a possible positive and negative link between CSR and earnings management by the moral licensing hypothesis (principal agent theory) and the moral track hypothesis (stakeholder theory). We focus on firm- and country-related moderator effects as contextual factors. Country-specific studies are separated in developed (Anglo-American and Continental European settings) and developing countries (African and Asian settings), code and case law regimes as well as the degree of shareholder protection and legal enforcement. In line with stakeholder theory, we stress that most of the included studies found a negative impact of CSR on earnings management with a focus on CSR performance and accruals-based earnings management. Other measures, for example, CSR reporting, sub-pillars of CSR performance, and real earnings management, are inconclusive due to reduced research activity. We do not find any structural changes between developed and developing countries, case and code law regimes, and regarding the strength of shareholder protection and legal enforcement. However, there are clear indications that corporate and country governance strengthens (weakens) the negative (positive) influence of CSR on earnings management. We stress major limitations of prior research and formulate useful recommendations for future research.
Keywords: 330; agency theory; CSR; CSR performance; CSR reporting; earnings management; financial reporting; stakeholder theory